Determinants of Corporate Fossil Energy Assets Impairment and Measurement of Stranded Assets Risk - Hao Zhao; Chuanqing Wu; Yang Wen (Energies, 2023)
Climate change and transition risks have become major issues concerning the sustainable development of human society today. And the stranded fossil energy assets generated in this context are gradually becoming an important factor affecting corporate development and the stability of financial markets. Based on the data of China’s A-share listed companies in the high-carbon industry from 1998 to 2021, a two-way fixed-effects model is used to study the determinants of corporate fossil energy asset impairment. Furthermore, a “two-stage estimation approach” is used to measure the risk of stranding corporate fossil energy assets The results show that: (1) climate transition risks are a significant cause of stranded corporate fossil energy assets; (2) the stranded risk of Chinese companies’ fossil energy assets has been oscillating upward over the past two decades; (3) the stranded risk has increased significantly after the “double carbon” target. Based on the above conclusions, this paper puts forward relevant suggestions from both government and enterprise perspectives.